Role of Radiation in Metachronous Multicentric Giant Cell Tumor of Bone: A Case Report - Nana Supriana; David Andi Wijaya (Perhimpunan Dokter Spesialis Onkologi Radiasi Indonesia (PORI), 2021)
Introduction: Giant cell tumor of the bone (GCTB) is a rare benign locally aggressive tumor. Surgical resection whenever feasible is treatment of choice for GCTB. Case Presentation: In this report the author will review a case of well locally controlled postoperative GCTB on left ilium bone after adjuvant radiation was delivered, with metachronous lesion on right calcaneus and distal tibia which appeared 9 years later.Conclusions: Radiation either in adjuvant setting or definitive in unresectable lesion could bring adequate local control.